Perencanaan Bisnis Pendidikan sebagai Strategi Pengembangan dan Keberlanjutan Lembaga Pendidikan - Rahmat Shulhani; Abdullah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
The increasingly dynamic educational environment demands that educational institutions have a well-planned and sustainable management strategy. One relevant strategic approach is the application of business planning to educational institution management. This study aims to analyze the role of educational business planning as a strategy for the development and sustainability of educational institutions, particularly in resource management, improving service quality, and strengthening institutional governance. This study employed a qualitative approach using a literature review method, examining various relevant scientific sources from the past five years, including journal articles, academic books, and reports from international institutions. The study results indicate that educational business planning contributes significantly to improving the effectiveness of human resources, finances, infrastructure, and educational technology management. Furthermore, business planning plays a crucial role in maintaining financial stability, strengthening managerial accountability, and enhancing educational institutions' adaptability to changing policies and societal demands. The discussion also reveals that the successful implementation of educational business planning is significantly influenced by leadership commitment, managerial capacity, and stakeholder involvement. This study confirms that educational business planning is not merely an administrative document, but rather a strategic instrument that supports the holistic development and sustainability of educational institutions. The findings of this study are expected to serve as a conceptual and practical reference for educational institution managers in designing effective, adaptive, and sustainable management strategies.